Vitamin D levels: its relationship to bone mineral density response and disease activity in premenopausal Malaysian systemic lupus erythematosus patients on corticosteroids. - Yeap, S.S.; Othman, A.Z.; Zain, A.A.; Chan, S.P. (Wiley, 2012)
AIM: To determine if baseline vitamin D levels would influence the gain in bone mineral density (BMD) in female systemic lupus erythematosus (SLE) patients on corticosteroids (CS) taking bone-active medication. METHOD: Premenopausal SLE patients participating in a trial assessing the efficacy of calcium alone, calcitriol and calcium, and alendronate and calcium, on BMD in patients on CS, were studied. Patients were randomly allocated to the treatment groups at the start of the study and followed up for 2 years. Serum 25-hydroxy vitamin D [25(OH)D] was measured at baseline. RESULTS: Thirty-eight patients were studied. One (2%) patient had osteoporosis, nine (24%) had osteopenia and all others had normal BMD. The mean baseline 25(OH)D levels were 21.6 ± 4.6 ng/mL (± 1 SD). Twelve (32%) patients had vitamin D deficiency [25(OH)D < 20 ng/mL]. There was a significant negative correlation between SLEDAI scores and 25(OH)D levels, that is, patients with high SLEDAI scores had significantly lower 25(OH)D levels (P = 0.033). Left femoral neck BMD was significantly lower in the deficient compared to insufficient group (P = 0.042). There was a trend toward better BMD gain at 2 years in the vitamin D insufficient compared to the deficient group, which did not reach statistical significance. CONCLUSION: This study showed that in female SLE patients, low vitamin D levels are associated with higher disease activity and suggests that patients who have higher vitamin D levels have a better BMD response during treatment with bone-active agents.